Geometric Programming: A Literature Review and Thematic Research Developments - Mas'ud, Syamsuddin (PT ARRUS Intelektual Indonesia, 2025)
This study examines Geometric Programming (GP) developments from 2014 to 2024 through a systematic literature review, focusing on theoretical advancements (e.g., successive convexification, weighted-sum fuzzy GP), model generalizations (e.g., Robust GP, Neutrosophic GP), and integration with AI/ML. Using thematic analysis of peer-reviewed publications and case studies, the results demonstrate GP’s unique capability to transform nonconvex problems into convex forms via logarithmic transformations, enabling efficient solutions for energy systems and logistics. While GP has achieved global maturity with tools like CVXPY and GPkit, its adoption in Indonesia remains limited despite relevance to archipelagic energy distribution and infrastructure planning (e.g., IKN). The study identifies critical requirements for local implementation: context-specific validation, enhanced computational capacity, and interdisciplinary collaboration, providing a strategic framework for GP’s evidence-based application in Indonesia.